Проверка:
верно.
Ответ: х = -3
Ответ:
Пошаговое объяснение:
(5-3х)/2 + (3+5х)/4 = (5-9х)/8 | * 8
4(5 - 3х) + 2(3 + 5х) = 1( 5-9х)
20 - 12х + 6 + 10х = 5 - 9х
-12х + 10х + 9х = 5 - 20 - 6
7х = -21
х = -21 : 7
х = -3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Проверка:
верно.
Ответ: х = -3
Ответ:
Пошаговое объяснение:
(5-3х)/2 + (3+5х)/4 = (5-9х)/8 | * 8
4(5 - 3х) + 2(3 + 5х) = 1( 5-9х)
20 - 12х + 6 + 10х = 5 - 9х
-12х + 10х + 9х = 5 - 20 - 6
7х = -21
х = -21 : 7
х = -3